استراتيجية التَّعلم بالأقران ودَورُها في تَذلِيل الصُّعوبات لذوي صُعوبات التّعلم في المدرسَة الابتِدَائية - هالة, سليمة (جامعة الوادي - University of Eloued, 2023)
تَعدّدت الاستراتيجيات الحديثة المتبعَة في المؤسسات التَّربوية لإنجاحِ العَمَليّة التَّعلِيميّة التّعلُمِيّة من جهة، وللتّكفل بذوي صُعوبات التَّعلم من جِهة أخرى، كون هذه الفِئة أصبحت لها فرصة التَّعايش مع أقرانهم في وسط تَعليمي واحد. الأمر الذي يُحَتّم على المعلِّم الإحاطة بمختلف الطرائق التَّدريسيّة الحديثة التي يجب الأخذ بها في مواقف معينة. التعلم بالأقران، من الطرائق الحديثة التي ذاع صيتها مؤخرًا نتيجة ما حققتهُ من نتائج مبهرة، جَعَلت من المتعلِّم مُعَلِّمًا وجعلت من المعلِّمِ محفزًا وموجهًا. وهذا ما تسمو إليه النَّظريات الحَديثة. فما المرادُ بالتَّعلّم بالأقرانِ؟ وما دورها في الوسَطِ المدرسي؟ وكيف تُسَاعد فِئة ذوي صُعُوبَات التَّعلم؟ It is well established that there are many modern strategies which are used in educational institutions to make the educational process successful on the one hand and to take care of learners with learning difficulties on the other hand. The latter has the opportunity to coexist with their peers in one educational environment which requires the teacher to be aware of the various modern teaching methods that must be adopted in certain situations. On the same line of thought, peer learning is one of the modern methods that have become popular recently due to the shift from teacher centeredness to learner centeredness which has extended the role of the teacher to a motivator and a guide. This is what modern theories call for. On this basis, this study aims to answer the following questions: What is meant by peer learning? What is its role in the school setting? And how do you help learners with learning difficulties?
مقال
Keywords: الاستراتيجيات الحديثة، التَّعلم بالأقران، ذوو صُعوبات التَّعلم; modern strategies, peer learning, people with learning disabilities.